Geological Knowledge: A Key to the Future of the Diamond Industry - Levinson, A.; Cook, F. (Geoscience Canada)

(untitled) (The Geological Association of Canada, 2000)
Summary The geological knowledge needed to find diamond deposits has increased substantially since the early 1950s and is now readily available in the public domain. This has resulted in the discovery of many new diamond deposits in the last 50 years and, therefore, an oversupply of rough diamonds at various times. Based on analogies with other mineral commodities, new diamond deposits will be found at an accelerated rate as diamond-related geological knowledge continues to expand and exploration methods are refined. In such circumstances, as with all commodities, in the long term (>20 years) new markets must be found to keep pace with increased production, otherwise there may be an ever-present concern based on oversupply.